Dynamic Scoring of Tax Reforms in the European Union - Salvador Barrios; Mathias Dolls; Anamaria Mafei; Andreas Peichl; Sara Riscado; Janos Varga; Christian Wittneben (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
This paper presents the first dynamic scoring exercise linking a microsimulation and a dynamic general equilibrium model for Europe. We illustrate our novel methodology by analysing hypothetical reforms of the social insurance contributions system in Belgium. Our approach takes into account the feedback effects resulting from adjustments and behavioural responses in the labour market and the economy-wide reaction to tax policy changes, essential for a comprehensive evaluation of the reforms. We find that the self-financing effect of a reduction in employers' social insurance contribution is substantially larger than that of a comparable reduction in employees' social insurance contributions.
Keywords: 330